OPENAI'S PLAGIARISM AGAINST STUDIO GHIBLI IN A COPYRIGHT LAW PERSPECTIVE - Cindy Swastika; Asri Elies Alamanda (Ajudikasi: Jurnal Ilmu Hukum, 2025)
This study examines OpenAI's plagiarism problem against Studio Ghibli from the perspective of copyright law. This problem leads more to the fundamental question, whether Studio Ghibli, which is currently widely used by humans easily produced by OpenAI, deserves copyright protection, considering that according to Law No. 28 of 2014 concerning Copyright, the so-called Creator is a person (several people) not a computer program.  The purpose of this study is to find out whether the use of Studio Ghibli's works by OpenAI without permission from the copyright holder falls into the category of plagiarism and copyright infringement, as well as to analyze the form of protection, certainty, and urgency of legal regulations in Indonesia through comparison with copyright regulations in other countries. The research method used is a normative legal method with a regulatory approach, a conceptual approach, and a comparative study. The results of the study show that OpenAI is considered to have plagiarized Studio Ghibli's work because it does not have official permission from the copyright holder. In Indonesia, there is no legal certainty regarding copyright protection for Studio Ghibli's works produced by OpenAI, because there are no specific rules governing it. In the ITE Law, OpenAI is only categorized as an electronic agent and is not recognized as a legal subject who can own copyrights. Comparison with other countries: The United States rejects copyrights for works that are not from humans, while the United Kingdom grants copyrights to OpenAI's developers. This research emphasizes the importance of the Indonesian government immediately formulating regulations that regulate the work produced by OpenAI, in order to have clear certainty and legal force.